Sustainable Development: Pregnancy Health - Bhavya. P; M.P Somashekar (PT FORMOSA CENDEKIA GLOBAL, 2024)
Pregnancy health is a critical component of sustainable development, encompassing the physical, emotional, and social well-being of expectant mothers and their offspring. Sustainable development goals emphasize the importance of ensuring healthy lives and promoting well-being for all at all ages, including during the prenatal period. This abstract explores the multifaceted aspects of pregnancy health within the framework of sustainable development, focusing on key areas such as maternal nutrition, access to quality healthcare services, maternal mental health, and environmental factors. Addressing pregnancy health not only contributes to the well-being of mothers and infants but also has far-reaching implications for the broader goals of sustainable development, including poverty reduction, gender equality, and economic growth. Strategies aimed at promoting pregnancy health should prioritize equity, accessibility, and sustainability to ensure positive outcomes for current and future generations. Employing a methodology grounded in simple random sampling, this research paper rigorously applies this approach to categorize and dissect the resultant data